ANALISIS UPAYA GURU DALAM MEMOTIVASI SISWA PADA PROSES PEMBELAJARAN SOSIOLOGI KELAS XI IPS2 - Berry Berry (Jurnal Pendidikan Sosiologi dan Humaniora, 2019)
The title of this research is "Analysis of Teacher Efforts to Manage Students in the Learning Process IPS2 Sociology Class XI". The purpose of this study was to determine and describe the efforts of teachers to motivate students in the learning process IPS2 sociology class XI. The approach used in this study is a qualitative approach with descriptive methods. The process of implementation is carried out with test instruments such as observation, interviews, and documentation.The results showed that the efforts of teachers to motivate students in the learning process of sociology in general have been implemented but have not carried out to the maximum. Constraints implementation of motivation by teachers, teacher attendance factors and methods of teaching, the student's social environment, and infrastructure are less supportive. The response of students is very worth noting that the way teachers deliver the material time in the classroom, because the volume is not loud teachers.